The Effect of Organizational Climate on Job Engagement with Job Satisfaction as A Mediator - Achsan, Salsa Shabila; Purwaningrum, Evi Kurniasari; Umaroh, Siti Khumaidatul (Utan Kayu Publishing, 2025)
The 2022 ASN work engagement survey, conducted by the Ministry of Administrative and Bureaucratic Reform of the Republic of Indonesia, shows that the percentage of ASN employees in administrative positions is lower than the percentage of employees in other positions. This study was conducted with the aim of empirically determining the influence of organizational climate on job engagement with job satisfaction as a mediator. The main hypothesis of this study is to determine whether job satisfaction can mediate the relationship between organizational climate and job engagement among civil servants. This study used a quantitative method with 183 civil servants as the research sample. This study employs three types of scales: Job Engagement UWES (Utrecht Work Engagement Scale), Organizational Climate using OCQ (Organizational Climate Questionnaire), and Job Satisfaction using MSQ (Minnesota Satisfaction Questionnaire). The SPSS 25 program for Windows was used to analyze research data using mediation regression techniques. The results of the study showed that organizational climate had a significant effect on job engagement with job satisfaction as a mediator with a p-value of 0.000 (p 0.05). The R value is 0.301. Job satisfaction as a mediator is very important because when there is a fair, open, and supportive work environment, it does not immediately make employees engaged in their work. Instead, when the work environment creates job satisfaction, this will encourage employees to be more emotionally, cognitively, and physically engaged in their work.